High linear growth rate of the pendulous lichen Usnea angulata Ach. in Sierra Chaco forest of central Argentina - Rodriguez, Juan Manuel (2011)
The purpose of this study was to identify the growth rate of the pendulous lichen Usnea angulata in the Sierra Chaco forest using transplanted and non transplanted thalli of different initial sizes. Fifty trees with U. angulata thalli were selected in a protected forest in central Argentina. On each Thallus, we selected the two longest branches (BSL and BL) and we cut fragments of 10 cm and 5 cm (FL and FSL) and attached them to the side. In addition, we randomly selected 96 thalli of U. angulata from the surrounding environment and we cut a fragment of 10 cm (FT). The fragments were attached to four different trees, and located in the same area. The linear growth of cut branches and fragments were measured for three years at intervals of six months. On average, the growth of U. angulata was 23.5 mm peryear. The FT growth rate was significantly higher. In Comparison with previous studies, the growth rate found is high. More studies are needed to determine the effect of the transplant method and the initial size of thalli at growth.